Mycotoxicological Profiling and Chromatographic Characterization of Retail Spices: A Mechanistic Evaluation of Microclimatic Packaging Dynamics on Aflatoxin Biosynthesis in Tropical Environments - Khrisna Agung Cendekiawan; Linda Suci Anggraeni; Firdha Aprillia Wardhani; Rina Fitriana (HM Publisher, 2026)
Spices produced in equatorial tropical climates are highly susceptible to mycotoxin contamination. Aflatoxin, a carcinogenic secondary metabolite synthesized by Aspergillus flavus and Aspergillus parasiticus, poses a severe global public health threat by inducing hepatotoxicity and transversion mutations. This study investigates the prevalence of toxigenic fungi and quantifies aflatoxin analogues in retail culinary spices across varying microclimatic environments. An observational surveillance study was conducted using purposive sampling of onion, turmeric, and pepper matrices from traditional markets and modern supermarkets. Fungal characterization utilized Potato Dextrose Agar and Nash-Snyder media. Precise quantification of Aflatoxins B1, B2, G1, and G2 was executed via high-performance liquid chromatography coupled with fluorescence detection (HPLC-FLD) and post-column derivatization. Mycological isolation confirmed pervasive colonization by Aspergillus flavus, A. niger, Penicillium spp., and Fusarium oxysporum. Method validation yielded excellent recovery (greater than 85%) and precision. Supermarket-sourced pepper (Sample C4) exhibited catastrophic hyper-contamination, with Aflatoxin B1 at 45.35 ppb and total aflatoxins at 99.35 ppb. Turmeric demonstrated intrinsic resistance, with maximum Aflatoxin B1 at 1.41 ppb. Non-parametric Spearman rank analysis revealed a significant positive correlation between trapped packaging micro-humidity and aflatoxin synthesis. In conclusion, modern non-vacuum packaging methodologies drastically elevate trapped micro-humidity, heavily driving the logarithmic growth and toxicological output of Aspergillus. Strict regulatory enforcement of storage humidity and water activity monitoring is urgently required in commercial retail sectors.